Public image campaigns by oil companies : a test of the political cost hypothesis. - Peh, Bee Hong. (2008)
Firm in the petroleum refining industry face considerable political scrutiny. This study examines whether such firms engage in earnings management by using discretionary accruals. It also explores whether they increase their level of disclosures through medium such as annual reports and press releases, in order to improve their public image.